“DESIGN AND TOPOLOGICAL OPTIMIZATION OF AN INTERNAL COMBUSTION ENGINE PISTON” - Badadhe R.B; Prof. Dr.R.R.Navthar (International Journal of Innovations in Engineering Research and Technology, 2023)
This project focuses on the stress distribution of the piston four stroke engines by using FEM. The main objective is to investigate and analyze the stress and maximum or minimum principal stresses distribution on engine piston at the real engine condition during combustion process. In this project, the wok is carried out to measure the stress on the top surface of the piston. In I.C. Engine piston is most complex and important part therefore for smooth running of vehicle piston should be in proper working condition. Pistons fail mainly due to mechanical stresses and thermal stresses. Analysis of piston is done with boundary conditions, which includes pressure on piston head during working condition the stress concentration on the piston head are reduces by optimization with using computer aided design; Solid work software the structural model of a piston will be developed. Furthermore, the FEM analysis is done using ANSYS workbench 21. A piston of 4 wheeler was analyzed and optimized for weight reduction in this study. The project describes the optimization techniques with using finite element analysis technique (FEM) to predict the higher stress and critical region on that component.